Legal Protection of Licensee and Licensor In Licensing Agreements - Rusmala Ratnawati, Erna Tri; Wiwik Handayani; Rizqi Samera Al Farizi (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2024)
This research discusses how the trademark license agreement can protect the licensee and licensor, the rights and obligations of the parties that arise in the trademark license agreement, and the legal consequences in the event of default. This research is normative research, with a statute approach to the problem. The analysis is focused on laws, regulations, documents, and other references related to brands and license contracts. The brand license agreement must comply with the principles of contract law because the principles of contract law are the foundation that must be obeyed by the parties so that it will not harm either party and can be implemented fairly. In addition, there needs to be an agreement that is mutually beneficial and does not burden each other. In a trademark license agreement, reciprocal rights and obligations occur between the licensee and the licensor. Both parties have mutual rights and both also have mutual obligations so a balanced bargaining position between licensee and licensor needs to be balanced so that there is no imbalance in rights and obligations. A brand license agreement will lead to disputes if the parties do not fulfill their rights and obligations as agreed. If one of them defaults, the other party can demand fulfillment of the engagement; fulfillment of the agreement with compensation; compensation; cancellation of the agreement; or cancellation with compensation. The first step that needs to be taken when a dispute occurs is to resolve the dispute by deliberation to reach a consensus. If not reached, dispute resolution can be seen in the trademark license agreement clause. Settlement of this dispute can be done both inside and outside the court. In addition to carrying out civil lawsuits, criminal charges can also be filed by the aggrieved party.